Dissipation and Persistence of Carbofuran and its Secondary Metabolite, 3-Ketocarbofuran in Brinjal (Solanum melongena) and Soil under Humid Tropical Climate - Jocephine, Jonip (Universiti Malaysia Sarawak (UNIMAS), 2020)
Carbofuran (2,3-dihydro-2,2-dimethyl-benzofuranyl-N-methylcarbamate) is a broad-spectrum insecticide-nematicide and appeared to be the most effective insecticide in controlling pests. Although it is banned in many countries in the world, it is widely used in Asia, Australia and South America. Carbofuran is a legally registered pesticide and commonly used in vegetable farming in Malaysia due to reasonable price in the market. In this study, the persistence and degradation of carbofuran were examined under humid tropic field and laboratory conditions. A total of 162 brinjal (Solanum melongena) plants were grown at Agricultural Research Centre, Semongok, Sarawak and carbofuran was applied when plants began to bear fruits. Prior to carbofuran residue analysis, the physicochemical properties of crop soil were studied. Modified QuEChERS method was used to determine the residue of carbofuran in soil and brinjal fruits and leaves. Meanwhile, in this study, the laboratory degradation of carbofuran under the effect of pH, moisture and temperature were studied using response surface methodology (RSM). A total of 24 experiments were carried out by incubating sets of sterilised soil for 24 hours according to inscribe central composite design (CCD). The percentage of carbofuran loss was calculated and fitted according to linear, interaction and quadratic models whereby its quality is measured on root mean square error (RSME) and regression coefficients, R2. Under field condition, in order to comply with the maximum residue limit (MRL) of 0.01 mg/kg, the pre-harvest interval suggested for brinjal was 28 days. The average half-life of carbofuran in soil, brinjal leaves and fruits are 1.24, 3.22 and 10.33 days, respectively. On the other hand, under laboratory condition, it was experimentally verified that linear model has the lowest RSME with an error of 5.82% and it is best describes the degradation of carbofuran. All three factors (pH, moisture and temperature) were found to correlate positively to the loss of carbofuran in soil. The soil pH establishes significant effect (p < 0.05) on the degradation which indicates chemical hydrolysis as the major pathway in this study.